Mask-associated dry-eye in COVID-19 pandemic: a case report and review of the literature - Momin, Sehrish Nizar Ali; Siddiqui, Rehman (Journal of the Pakistan Medical Association, 2022)
Mask-Associated Dry Eye (MADE) has been showing a rising trend during COVID 19 pandemic. This phenomenon seems inevitable, as wearing a face mask is a requisite part of personal protective measures to suppress of the spread of virus. However, simple expeditious awareness among health care staff, including the general population, can decrease the incidence. Keywords: Dry eye disease, COVID 19 Pandemic, Post-operative complications.